2018
DOI: 10.14814/phy2.13878
|View full text |Cite
|
Sign up to set email alerts
|

A selective antagonist of prostaglandin E receptor subtype 4 attenuates abdominal aortic aneurysm

Abstract: Abdominal aortic aneurysm (AAA) is a progressive disease that has an increasing prevalence with aging, but no effective pharmacological therapy to attenuate AAA progression is currently available. We reported that the prostaglandin E receptor EP4 plays roles in AAA progression. Here, we show the effect of CJ‐42794, a selective EP4 antagonist, on AAA using two mouse models (angiotensin II‐ and CaCl2‐induced AAAs) and human aortic smooth muscle cells isolated from AAA tissue. Oral administration of CJ‐42794 (0.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…However, the role of EP4 in pathological vascular remodeling remains uncertain. It has been reported that inhibition of EP4 attenuates aortic aneurysm formation (10)(11)(12), whereas the lack of EP4 in hematopoietic cells is associated with increased prevalence and severity of AngII-induced aortic aneurysms (13).…”
mentioning
confidence: 99%
“…However, the role of EP4 in pathological vascular remodeling remains uncertain. It has been reported that inhibition of EP4 attenuates aortic aneurysm formation (10)(11)(12), whereas the lack of EP4 in hematopoietic cells is associated with increased prevalence and severity of AngII-induced aortic aneurysms (13).…”
mentioning
confidence: 99%
“…In a Japanese study it was observed that the PA aneurysm area, in comparison to non-PAA areas, showed increased EP4 receptor (for the cyclooxygenase-2-dependent PGe2) expression [2]. The increased expression of that receptor is also described in non-striated muscle cells as well as in macrophages in abdominal aortic aneurysm areas [21][22][23]. PGe2, via the eP4 receptor, increases the activity of metalloproteinase 2 and the production of interleukin 6, causing increased degradation of elastic fibers redounding to the AAA progression [21,22].…”
Section: Discussionmentioning
confidence: 98%
“…The increased expression of that receptor is also described in non-striated muscle cells as well as in macrophages in abdominal aortic aneurysm areas [ 21 23 ]. PGE2, via the EP4 receptor, increases the activity of metalloproteinase 2 and the production of interleukin 6, causing increased degradation of elastic fibers redounding to the AAA progression [ 21 , 22 ]. Nonsteroidal anti-inflammatory drugs and selective COX-2 inhibitors suppress PGE2 synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…In human AAA samples, higher EP4-receptor expression versus normal samples was demonstrated by real-time PCR studies (Camacho et al, 2013). Exposure of aortic smooth muscle cells (SMCs) and macrophages derived from human AAA preparations to EP4-receptor antagonists (CJ-42794 or ONO-AE3-208) decreased MMP activation and proinflammatory cytokines secretion (Cao et al, 2012;Yokoyama et al, 2012;Mamun et al, 2018). These findings suggested that EP4-receptor antagonists could be a therapeutic target for the treatment of AAA.…”
Section: Cardiovascular Systemmentioning
confidence: 98%
“…These findings suggested that EP4-receptor antagonists could be a therapeutic target for the treatment of AAA. Similarly, administration of EP4-receptor antagonist or deletion of the EP4 receptor in ApoE knockout mice reduced AAA formation via diminution of cytokine/chemokine levels and MMP activities ( Cao et al, 2012 ; Yokoyama et al, 2012 ; Mamun et al, 2018 ). However, there is one contradictory study performed in hyperlipidemic mice.…”
Section: Cardiovascular Systemmentioning
confidence: 99%